Toxicological Studies of popular eye cosmetic used world wide (Bangladesh Journal of Medical Science, 2018)
Background and Objective: Present research work was designed and conducted to verify the safe use of kajal, a popular eye cosmetic, which is widely used to beautify eyes throughout the world especially in South Asia and Middle East region.Material and Method: The toxicological studies were conducted in experimental animals for a period of 90 days to clarify misleading thoughts associated with its long term use including lead toxicity. The study was carried out in Albino rats of Wister strain and New Zealand White rabbits. Hashmi kajal dibya (net weight 4.25g), an eye cosmetic manufactured by M/s A.Q. and company international Pakistan was used as source for study. The ingredients claimed by the manufacturer are zinc oxide, wax, cinnamonum camphora, processed carbon black and clarified butter.Result: The elemental analysis resulted in presence of zinc 9.56%, lead 0.09% and total ash 41.01%, while sulfur, antimony, mercury and arsenic were not detected in the sample. The sub-chronic toxicological studies revealed that no toxicological effects were found in experimental animals. All the animals of test and control groups exhibited normal physiological activities and an increase in body weights. Lead and Zinc levels remained constant throughout the experimental period and no mortality was recorded. Furthermore, liver and kidney function tests were normal, indicating non-toxic effect of the kajal on vital organs.Conclusion: So it can be assumed that this eye cosmetic is non-toxic and can be used safely in humans.Bangladesh Journal of Medical Science Vol.18(1) 2019 p.118-123